Planetary topography measurement by descent stereophotogrammetry. (August 2021) - Brydon, G.; Persaud, D.M.; Jones, G.H.
Abstract: Digital Terrain Models (DTMs) provide valuable insights into the nature of solar system surfaces, facilitating geological analysis, landing site selection and characterisation, and contextualising in situ measurements. For missions to solar system bodies for which orbiters and soft landed platforms are technologically or financially challenging to achieve, low mass descent or ascent probes (e.g. planetary penetrators) provide an alternative means by which to access the atmosphere and/or surface, and a platform from which to image the surface from a range of altitudes and perspectives. This paper presents a study into the concept of large-coverage descent stereophotogrammetry, whereby the stereo geometry of vertically offset wide-angle descent images is used to measure surface topography over a region of large extent. To do this, we simulate images of Mars' Gale Crater using a large coverage, high resolution DTM of the area, and derive topographic measurements by stereo matching pairs of simulated images. These topographic measurements are compared directly with the original DTM to characterise their accuracy, and dependence of elevation measurement accuracy on stereo geometry is thus investigated. For a stereo pair with a given altitude (corresponding to the altitude of its lower image), error in elevation measurement is found to have its minimum value for surface at a horizontal distance between 1 and 3 times the altitude. For a point on the surface with given horizontal distance from the imaging location, a stereo imaging altitude between 0.2 and 0.5 times this distance is found to achieve best elevation measurement accuracy. Surface appearance, and its change between two images of a stereo pair, is found to have a significant impact on stereo matching performance, limiting stereo baseline length to an optimum value range of 0.2–0.4 times the lower image's altitude, and resulting in the occurrence of occlusions and blind spots, particularly at oblique viewing angles. Highlights: Wide-angle descent stereo is an effective means of planetary topography measurement. A novel imaging and stereo pipeline is simulated to quantify measurement accuracy. Optimal stereo geometries are described for maximising measurement accuracy. The technique could be applied to a wide range of planetary descent/ascent probes.